2013
DOI: 10.1097/cej.0b013e3283592c46
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of carcinogenic human papillomavirus types from mother to child

Abstract: Currently, human papillomavirus (HPV) research focuses on HPV infection in adults and sexual transmission. Data on HPV infection in children are slowly becoming available. It is a matter of debate whether mother-to-child transmission of HPV is an important infection route and whether children born to HPV-positive mothers are at a higher risk of HPV infection compared with children born to HPV-negative mothers. The objective of this meta-analysis is to summarize the published literature on the extent to which g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…A recent meta-analysis on 3,128 mother/child pairs showed that children of HPV-positive mothers were 33% more likely to be HPV-positive than children born to HPV-negative mothers. This risk was even higher (45%) when only HR-HPV infections were considered [88]. It was estimated that vertical HPV transmission was the most likely mode of virus acquisition in 20% of these children, and other plausible explanations included a higher infection rate from the mother to her child during the early nursing period [88].…”
Section: The New Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis on 3,128 mother/child pairs showed that children of HPV-positive mothers were 33% more likely to be HPV-positive than children born to HPV-negative mothers. This risk was even higher (45%) when only HR-HPV infections were considered [88]. It was estimated that vertical HPV transmission was the most likely mode of virus acquisition in 20% of these children, and other plausible explanations included a higher infection rate from the mother to her child during the early nursing period [88].…”
Section: The New Hypothesismentioning
confidence: 99%
“…This risk was even higher (45%) when only HR-HPV infections were considered [88]. It was estimated that vertical HPV transmission was the most likely mode of virus acquisition in 20% of these children, and other plausible explanations included a higher infection rate from the mother to her child during the early nursing period [88]. Another recent meta-analysis showed that the pooled percentage of antenatal vertical HPV transmission was 4.9% (95% CI 1.651–9.849) among HPV-positive mothers.…”
Section: The New Hypothesismentioning
confidence: 99%
“…The risk was 45% when only HR-HPV infection was considered. [33]. A recent meta-analysis calculated that the pooled percentage of antenatal vertical HPV transmission was 4.936% (95% CI 1.651–9.849) [38].…”
Section: Other Possible Transmission Routes Of Hpv Infectionmentioning
confidence: 99%
“…This can be rather due to geographical differences in HPV prevalence, distribution of HPV variants, susceptibility towards HPV infection or lifestyle and sexual behaviour as well [5]. Modes of transmission of HPV in colorectal cancer have been contentious; however, anal transmission by sexual behaviour, retrograde viral transmission from the anogenital area [27] or vertical transfer from HPV infected mother [28] has been anticipated. However, similar colonal and rectal viral detection rates in the current as well as previous studies suggest that HPV might not be a result of retrograde viral transmission from the anogenital areas [8,9].…”
Section: Discussionmentioning
confidence: 96%